2018
DOI: 10.1016/j.healun.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Heart Donor Assessment Tool (PH-DAT): A novel donor risk scoring system to predict 1-year mortality in pediatric heart transplantation

Abstract: This novel pediatric-specific, donor risk scoring system appears capable of predicting post-transplant mortality. Although the PH-DAT may benefit organ allocation and assessment of recipient risk while controlling for donor risk, prospective validation of this model is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 22 publications
0
57
0
Order By: Relevance
“…Multiple donor factors have previously been identified as risk factors for PGD, including donor age, donor/recipient size mismatch, donor CPR, and markers of cardiac dysfunction (EF, need for inotropes) . Notably, none of these were found to be significant risk factors for the development of PGD in our cohort.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Multiple donor factors have previously been identified as risk factors for PGD, including donor age, donor/recipient size mismatch, donor CPR, and markers of cardiac dysfunction (EF, need for inotropes) . Notably, none of these were found to be significant risk factors for the development of PGD in our cohort.…”
Section: Discussionmentioning
confidence: 69%
“…[19][20][21][22][23] A previous assessment of PGD from our institution 4 in an earlier era Multiple donor factors have previously been identified as risk factors for PGD, including donor age, donor/recipient size mismatch, donor CPR, and markers of cardiac dysfunction (EF, need for inotropes). 13,27,28 Notably, none of these were found to be significant with improved survival (although this did not achieve statistical significance). Although PGD was previously thought to impact survival primarily within a 30-day postoperative period, 29 we found severe PGD to negatively impact survival for approximately 8 months after OHT.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Easterwood et al demonstrated no difference in graft survival following utilization of donor hearts previously refused using these codes despite a higher incidence of positive blood cultures, Public Health Service increased‐risk status, cardiac arrest, and cardiopulmonary resuscitation. Similarly, a recently derived Pediatric Heart Donor Assessment Tool demonstrated acceptable predictive capabilities for 1‐ and 5‐year post‐transplant morality, with ischemic times greater than 4 hours, donor cerebrovascular accident, donor‐to‐recipient height ratios >1.2, severe renal insufficiency, and left ventricular ejection fraction of <50% as the only variables that persisted in multivariate analyses . As described above, our recipient’s heart was previously refused for 197 different potential recipients despite a brief period of CPR and a normal LVEF without need for inotropic support.…”
Section: Discussionmentioning
confidence: 75%
“…Easterwood et al 5 ventricular ejection fraction of <50% as the only variables that persisted in multivariate analyses. 6 As described above, our recipient's heart was previously refused for 197 different potential recipients despite a brief period of CPR and a normal LVEF without need for inotropic support. This suggests donor influenza infection as the only discernible indication for refusal.…”
Section: Discussionmentioning
confidence: 99%